Abnormalities of intrinsic brain activity in irritable bowel syndrome (IBS): A protocol for systematic review and meta analysis of resting-state functional imaging. Issue 21 (28th May 2021) - Li, J.; Wang, C.; Li, Z.M.; Fu, B.; Han, Q.; Ye, M.
Abstract: Background: Irritable bowel syndrome (IBS) is one of the most common functional gastrointestinal (GI) disorders affecting up to 11.5% of the general global population. The brain–gut axis has been shown to play an important role in the pathogenesis of IBS. Several studies confirmed that intrinsic brain abnormalities existed in patients with IBS. But, studies of abnormal regional homogeneity (ReHo) in IBS have reported inconsistent results. The objective of this protocol is to conduct a meta-analysis using the Seed-based d mapping software package to identify the most consistent and replicable findings of ReHo in IBS patients. Method: We will search the following three electronic databases: MEDLINE, EMBASE and Web of Science. The primary outcome will include the peak coordinates and effect sizes of differences in ReHo between patients with IBS and healthy controls from each dataset. The secondary outcomes will be the effects of age, illness severity, illness duration, and scanner field strength. The SDM approach was used to conduct voxel-wise meta-analysis. Whole-brain voxel-based jackknife sensitivity analysis was performed to conduct jackknife sensitivity analysis. A random effects model with Q statistics is used to conduct heterogeneity and publication bias between studies and meta-regression analyses were carried out to examine the effects of age, illness severity, illness duration, and scanner field strength. Results: The results of this paper will be submitted to a peer-reviewed journal for publication. Conclusion: This research will determine the consistent pattern of alterations in ReHo in IBS patients.